Ways of images with Chema Madoz (Journal of Parents and Teachers, 2025)
The author of this article shows the exciting work of Chema Madoz, photographer. With his work she has prepared five activities to do in the arts and crafts class: association of images, making a way of images, exhibition and reading of images, images of one’s own way and assessment by analogies. She encourages everyone to collect images, to explore the world of Contemporary Arts to find out new ways to carry out fascinating activities to make both teachers and students enjoy.
Keywords: didactics; arts and crafts; photography; images